10^2 + 4 * (6 + 3) - 27 ÷ (9 - 6) = 127
=100 + 4 * 9 - 27 ÷ 3
multiplication & division before addition and subtraction (order of operations rules, PEMDAS)
100 + 36 - 9= 127
136 - 9= 127
127= 127
Place a set of parentheses around (6+3) and (9-6).
Hope this helps! :)
Answer:
equation 2into minus 3 into equation 1
8x+ 3y= -28
-3x-3y=18
----------------
5x=10
x =2
put value of y in equation 2
8 into 2+3y=-28
16+3y= -28
3y= -28+16
3y= -12
y= -4
3sinx+1=sinx
2sinx+1=0
2sinx=-1
sinx=-1/2
x=sin^-1 (1/2) = 30 =
![\pi](https://tex.z-dn.net/?f=%20%5Cpi%20)
/6 (when finding the inverse, always take the positive value, ignore the negative sign)
x is therefore negative in 3rd and 4th quadrant
Therefore values of x are:
180+30=210 = 7
![\pi](https://tex.z-dn.net/?f=%20%5Cpi%20)
/6
360-3=330 = 11
![\pi](https://tex.z-dn.net/?f=%20%5Cpi%20)
/6
What you must do in this case is to find the roots of the polynomial.
We have then:
x ^ 2 + 20x + 100 = 36
Rewriting:
x ^ 2 + 20x + 64 = 0
The values of the roots are:
x1 = -4
x2 = -16
Remember that the values of the roots are what make the polinome zero
Answer:
x1 = -4
x2 = -16